Cross-border reproductive care for law evasion: should physicians be allowed to help infertility patients evade the law of their own country?. (July 2016) - Van Hoof, Wannes; Pennings, Guido; De Sutter, Petra
Abstract: There are fundamental differences between countries with regard to legislation on assisted reproduction. Many infertility patients are looking to evade the law of their own country and make use of reproductive services abroad. The role of the local physician in cross-border reproductive care for law evasion has been characterized as "channeling local patients to foreign medical establishments" and "against the spirit and essence of the law". The logical view is that by supporting CBRC for law evasion, physicians are essentially supporting immoral behavior. We will tackle this position on two levels. First, we will argue that governments should generally be tolerant toward people with different positions on assisted reproduction. Second, we will show that contributing to cross-border reproductive care for law evasion is not necessarily immoral, because the prima facie wrongness of complicity in law evasion can be outweighed by the fact that physicians should act in the best interest of the patient. Several countries have tried to prevent local physicians from helping patients to make use of reproductive services abroad, but they should rather leave it up to the individual physicians to decide whether or not to support a particular patient.